Best Practices in Interconnecting Sharia Arbitration Norms: A Comparative Analysis of Indonesia and Europe - Suadi, Amran; Affandi, Muchammad Taufiq (Universitas Muhammadiyah Surakarta, 2024)
This paper explores the intricate process of interconnecting Sharia law with the legal systems of Europe, with a focus on the theoretical perspectives presented by Robert Alexy and H.L.A. Hart. It delves into the complexity and challenges associated with this integration and identifies key points of contention and opportunities. Notable challenges include overcoming the negative perceptions of Sharia law within Western legal circles, recognizing the diverse interpretations of Sharia, and harmonizing capitalist and Shariacompliant economic principles. The paper emphasizes the significance of interconnecting Sharia law with European legal systems, particularly within the realm of economic law, where concepts of justice, ethics, and Sharia's intricate provisions come into play. Using the theoretical frameworks of Alexy and Hart, the paper operationalizes the variables of